2009
DOI: 10.1007/s11357-008-9083-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased NHE8 isoform expression and defective acidification in proximal convoluted tubules of senile rats

Abstract: We have previously found that aged rats show decreased proximal acidification without changes in NHE3 or V-H + ATPase expression in brush border membrane vesicles. However, we did not identify any mechanism underlying these observations. The aim of the present work was to evaluate some of the regulatory systems of proximal acidification that could be affected by aging. We measured plasma concentrations of parathyroid hormone (PTH) and the amount of cAMP in the renal cortex of young and old Wistar rats. PTH pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Decreased expression of NHE8 protein and message is associated with defective acidification in proximal convoluted tubules of aged rats (Fiori et al, 2009). In intestinal inflammation, both NHE3 and NHE8 are decreased, accounting for reduction of Na absorption in inflammatory diarrhea.…”
Section: Slc9a/nhe Familymentioning
confidence: 99%
“…Decreased expression of NHE8 protein and message is associated with defective acidification in proximal convoluted tubules of aged rats (Fiori et al, 2009). In intestinal inflammation, both NHE3 and NHE8 are decreased, accounting for reduction of Na absorption in inflammatory diarrhea.…”
Section: Slc9a/nhe Familymentioning
confidence: 99%
“…NHE1 is present in the basolateral membrane of most segments of the renal tubule. NHE8 is expressed in the apical membrane of renal proximal tubules in neonates [25] and aged rats [26 • ] and has a similar function to NHE3 [26 • ,27]. However, it is mostly intracellular in adults [28 • ].…”
Section: Introductionmentioning
confidence: 99%
“…NHE8 expression in the intestine is age dependent, with the highest expression in young animals ( Xu et al, 2005 ; Xu et al, 2008 ; Fiori et al, 2009 ; Xu et al, 2012 ). Several studies have shown that the binding of the Sp3 transcriptional factor to the NHE8 basal promoter is crucial for the transcriptional regulation of NHE8 ( Xu et al, 2009 ; Xu et al, 2010a ; Xu H. et al, 2015 ).…”
Section: Nhe8 In the Gastrointestinal Tractmentioning
confidence: 99%